2017
DOI: 10.1080/00224499.2017.1373267
|View full text |Cite
|
Sign up to set email alerts
|

A Dyadic Approach to Understanding the Link Between Sexual Functioning and Sexual Satisfaction in Heterosexual Couples

Abstract: Researchers have demonstrated that several dimensions of sexual functioning (e.g., sexual desire, arousal, orgasm) are associated with the sexual satisfaction of individuals in a committed mixed-sex (male-female) relationship. We extended this research by comparing a dyadic model that included both own (i.e., actor effect) and partner (i.e., partner effect) domains of sexual functioning to an individual model that included only actor effects. Participants were 124 mixed-sex couples who completed online measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 77 publications
1
17
0
2
Order By: Relevance
“…Around a third of the patients considered their sexual life to be satisfactory, while more than half reported also being satisfied with their relationship with their partner. Although a relationship was observed between sexual satisfaction and relationship satisfaction, also reflected in other studies, [44][45][46] the latter was not associated with the overall IIEF score or with any of its subscale scores. While psychological distress was present, in very few of the evaluated men did it achieve clinically significant levels.…”
Section: Discussionsupporting
confidence: 41%
“…Around a third of the patients considered their sexual life to be satisfactory, while more than half reported also being satisfied with their relationship with their partner. Although a relationship was observed between sexual satisfaction and relationship satisfaction, also reflected in other studies, [44][45][46] the latter was not associated with the overall IIEF score or with any of its subscale scores. While psychological distress was present, in very few of the evaluated men did it achieve clinically significant levels.…”
Section: Discussionsupporting
confidence: 41%
“…Dyadic models using APIM typically outperform uni-partner models when predicting relationship-relevant variables (e.g. Pascoal et al, 2018). Application of this dyadic model to reasoned action approaches to safer sex behavior would allow for estimation of the mutual contributions of each partners' characteristics (e.g.…”
Section: A Dyadic Approach To Safer Sex Decision-makingmentioning
confidence: 99%
“…Within close-relationship research, it has long been recognized that an individual’s attitudes and behaviors can have a direct, and even causal, influence on the attitudes and behaviors of their partner(s) (Kelley et al, 1983). For example, recent research has demonstrated that women’s sexual dysfunction predicts men’s sexual satisfaction over-and-above men’s own sexual dysfunction, and vice versa (Pascoal et al, 2018). Similarly, Vowels and Mark (2020) found a predictive link between relationship satisfaction and sexual satisfaction in both members of mixed-sex couples.…”
Section: A Dyadic Approach To Safer Sex Decision-makingmentioning
confidence: 99%
“…Changes in sexual desire may help explain why COVID-19-related lifestyle changes are associated with worse relationship functioning. Research has shown that individuals with lower sexual desire and sexual activity reported less sexual and relationship satisfaction (Dosch et al, 2016;Mark, 2014;Pascoal et al, 2018;Santtila et al, 2007). A similar trend was observed at the onset of the pandemic, such that individuals who experienced declines in their sexual desire also reported declines in intercourse frequency (Karsiyakali et al, 2021;Lehmiller et al, 2021).…”
Section: Relationship Functioningmentioning
confidence: 75%